Traffic-related air pollution and solid organ transplant failure in Great Britain: A retrospective cohort study. (September 2018) - Pierotti, Livia; Schofield, Susie J.; Collett, Dave; Fecht, Daniela; De Hoogh, Kees; Hansell, Anna L.; Dark, John; Cullinan, Paul
Abstract: Background: Limited evidence suggests that exposure to traffic related air pollution is associated with graft failure among lung transplant recipients. We explored associations between pollution and transplant failure among lung and other solid organ transplant recipients in Great Britain through a retrospective cohort study. Methods: All patients who received a lung, heart, liver, or kidney transplant between 2000 and 2008 in Great Britain were included, as recorded in the National Health Service Blood and Transplant (NHSBT) register and followed to March 2015. Using residential addresses at time of transplant we calculated distance to nearest (major) road and modelled annual average exposures to airborne nitrogen oxides and particulate matter of diameter ≤10µm and ≤2.5µm for each transplant recipient. All-cause mortality or graft failure (kidney) during follow up was the main outcome; median follow-up was around 10 years for each organ type. We fitted Cox regression models with adjustment for age, sex, year of transplant and donor age/smoking status. Results: 780 lung, 1213 heart, 3650 liver and 11966 graft kidney transplant patients were analysed. We did not find any consistent associations between mortality or graft failure and any of the analysed air pollutants or road metrics. Although, exposure to particulate matter was associated with renal transplant failure in univariable analyses but not after adjustment for confounders. Conclusions: Our analysis does not confirm previously reported associations between traffic-related air pollution exposure and the risk of transplant failure. Highlights: Relationship between air pollution and organ transplant failure. Solid organ transplants to assess the specificity have been included. Failed to find associations.